Analysis of Controlling Communication Style in The Framework of Fritz Heider's Attribution Theory - Hotami, Raulia Rifa; Yanuar, Fit; Widaningsih, Titi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
Controlling style communication style is a communication approach characterized by dominance in decision-making, one-way communication, and minimal space for employees to be actively involved in the work process. Leaders who use this style tend to impose their views without considering input from employees. In the context of an organization, this communication style can create negative perceptions among employees, especially if employees feel that the decisions made do not consider real conditions in the field. This study aims to analyze the application of controlling style communication style in an organization called CV Anugrah Win Sejahtera, using Fritz Heider's Attribution Theory. The method used is descriptive qualitative, with data collection techniques through in-depth interviews and direct observation of employees and leaders in the company. Attribution theory is used to understand how employees interpret or assess the leader's communication style. The results of the study show that the controlling style communication style by leaders gives rise to employee perceptions that the decisions taken are authoritarian and do not pay attention to the reality they face. Employees feel less appreciated, not involved in decision-making, and lose motivation. This has an impact on less harmonious working relationships and reduces the level of employee emotional participation in the company. Based on attribution theory, employees tend to attribute the leader's communication style as a form of overly dominant control, which causes feelings of frustration and a lack of belonging to the company.